The larvae of Limnephilus minos Malicky 1970 and Mesophylax impunctatus aduncus (Navás 1923) (Trichoptera: Limnephilidae), including a discriminatory matrix for the Greek limnephilid larvae with multifilament gills - Waringer, Johann; Malicky, Hans (Zootaxa, 2019)
Limnephilus minos Malicky 1970 is a micro-endemic caddisfly restricted to the Greek island of Crete. Mesophylax impunctatus aduncus (Navás 1923) is known from Turkey and the southern Balkan peninsula; Greek records range from islands close to the mainland and Skiros to the northern mainland, and Attica. This paper describes the previously unknown larvae of both taxa. Information on the morphology of the 5th larval instar of each taxon is given, and the most important diagnostic characters are illustrated. A discriminatory matrix for the Greek limnephilid larvae with multifilament gills is also provided. In the context of existing identification keys, the larva of L. minos belongs to the group of Limnephilini larvae where face setae are lacking on the mid- and/or hind femora; the species keys together with L. auricula Curtis 1834 and can be separated from the latter species by setae present between the primary setae on the distal section of mid- and hind trochanters. In contrast, face setae are present on the mid- and/or hind femora in M. impunctatus aduncus. Its larva can be easily identified by the fact that 3 or more ventral-edge setae are present on the midfemur, by setae present on both sides of the anal slit, and by its grazer-type mandible lacking terminal teeth.